Arab Tribes’ Movement , Uprising "in Lower Egypt and Upper Egypt" in the Second Half of the Seventh Century AH - Hassan, Qader Muhammad; Ahmed, Revan Ghazy (Zanco Journal of Human Sciences, 2021)
The study of Arab tribes' movement , uprising"in Lower Egypt and Upper Egypt" in the second half of the seventh century AH in the Mamluk sheds highlight on the most important movement , uprising that occurred in these cities during the reign of the Mamluk state and touched upon their intense activities against the Mamluk state that lasted about three centuries, and the reason for these circumstances is due to the influence and values of each of these tribes, and the statement of the revolutions of the Arab tribes who refused to recognize the authority of the Mamlukes, caused by the problem of the dualistic mentalities and conflicting minds of each of them. They have the right to transcend their borders, in return for the mentality of the Arab tribes or the Arab tribes of Upper Egypt and Lower Egypt, which represented their right to rule from the Mamlukes,the ascendants, the usurpers of the throne from the House of Ayub. Negative backgrounds on the country, and the most important negative consequences of those revolts is the destruction of the Mamluk Egyptian economy on the social side, and its impact on the country as well.